The status of public libraries in the Philippines with special reference to provincial and city libraries - David, Conrado D.; Picache, Ursula G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1974)
This paper deals extensively on the actual conditions obtaining in thirty-three provincial and nineteen regularly organized city libraries administered and supervised by the National Library thru its Extension Division. The study includes such aspects of the public library as building, equipment, collection, readership, personnel, and the budget, and the financial support given to it by the local officials.
While the discussion centers mainly on the provicial and city libraries, municipal and barrio libraries also under the administration and supervision of the National Library, are likewise mentioned in passing. The setups in the Manila City Libraries, and of the Thomas Jefferson Cultural Center (USIS) are also briefly taken up.
In the absence of any specific law setting standards for our public libraries, the investigator, after presenting the facts and figures, will, of course, leave the reader to draw his own conclusions. It is important to stress one thing at the start: the librarians concerned are the first to admit that their libraries, based on the need of their clientele, can stand a great deal of improvement. Others are operating definitely under substandard conditions.
The investigator concludes his paper with his own recommendations on how to solve some of the problems confronting the librarians which ultimately lead to their basic concern; the improvement and expansion of public library service in the country.
Thesis (M.L.S)-- University of the Philippines, Diliman
Typescript.
Vita
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Public libraries--Philippines.